The Implications of Nahum 1:12-2:2 for the Case of Religious Discrimination in Indonesia - Mokoagouw, Henny; Rouw, Randy Frank; Brown, Lisa (Sekolah Tinggi Teologi Simpson Ungaran, 2024)
The book of Nahum is full of the news of God’s judgment upon Nineveh; this book looks gloomy and hopeless, but one will find the theme of restoration as well. This article analyzes Nahum 1:12-2:2 as a basis for addressing the problem of religious discrimination in Indonesia. Using the literature study method, the results from this article are divided into theological and practical implications. Theologically, the text of Nahum 1:12-2:2 provides believers with hope for restoration from the One who brings true restoration: God himself. Practically, this text encourages God's people to remain steadfast and not despair but have hope, for there will come a time when God restores them. In addition, when true restoration occurs, believers should return to God and not continue to indulge themselves in pleasure and self-satisfaction.